The Ultraviolet Slopes of Early Universe Galaxies: The Impact of Bursty Star Formation, Dust, and Nebular Continuum Emission - Desika Narayanan; Daniel P. Stark; Steven L. Finkelstein; Paul Torrey; Qi Li; Fergus Cullen; Micheal W. Topping; Federico Marinacci; Laura V. Sales; Xuejian Shen; Mark Vogelsberger (The Astrophysical Journal)
JWST has enabled the detection of the ultraviolet (UV) continuum of galaxies at z > 10, revealing extremely blue, potentially dust-free galaxies. However, interpreting UV spectra is complicated by the well-known degeneracy between stellar ages, dust reddening, and nebular continuum. The main goal of this paper is to develop a theoretical model for the relationship between galaxy UV slopes ( β ), bursty star formation histories, dust evolution, and nebular contributions using cosmological zoom-in simulations. We build a layered model where we simulate increasingly complex physics, including the impact of (i) unattenuated intrinsic stellar populations, (ii) reddened populations using a new on-the-fly evolving dust model, and (iii) populations including dust and nebular continuum. Unattenuated stellar populations with no nebular emission exhibit a diverse range of intrinsic UV slopes ( β _0 ≈ −3 → −2.2), with an inverse correlation between UV slope and specific star formation rate. When including dust, our model galaxies demonstrate a rapid rise in dust obscuration between z ≈ 8 and 10. This increase in dust mass is due to high grain–grain shattering rates, and enhanced growth per unit dust mass in very small grains, resulting in UV-detected galaxies at z ∼ 12 descending into Atacama Large Millimeter/submillimeter Array–detectable galaxies by z ∼ 6. The rapid rise in dust content at z ≈ 8–10 leads to a systematic reddening of the UV slopes during this redshift range. Nebular continuum further reddens UV slopes by a median Δ β _neb ≈ 0.2–0.4, though notably the highest-redshift galaxies ( z ≈ 12) are insufficiently blue compared to observations; this may imply an evolving escape fraction from H ii regions with redshift.